How health systems approached respiratory viral pandemics over time: a systematic review - Walter Ricciardi (BMJ Publishing Group, 2020)
Background Several healthcare systems facing respiratory viral infections outbreaks, like COVID-19, have not been prepared to manage them. Public health mitigation solutions ranging from isolation of infected or suspected cases to implementation of national lockdowns have proven their effectiveness for the outbreak’s control. However, the adjustment of public health measures is crucial during transition phases to avoid new outbreaks. To address the need for designing evidence-based strategies, we performed a systematic review to identify healthcare systems interventions, experiences and recommendations that have been used to manage different respiratory viral infections outbreaks in the past.Methods PubMed, Web of Science, Scopus and Cochrane were searched to retrieve eligible studies of any study design, published in English until 17 April 2020. Double-blinded screening process was conducted by titles/abstracts and subsequently eligible full texts were read and pertinent data were extracted. When applicable, quality assessment was conducted for the included articles. We performed a narrative synthesis of each implemented public health approaches.Results We included a total of 24 articles addressing the public health approaches implemented for respiratory viral infections outbreaks for COVID-19, influenza A H1N1, MERS and severe acute respiratory syndrome . The identified approaches are ascribable to two main categories: healthcare system strategies and healthcare provider interventions. The key components of an effective response on respiratory viral outbreaks included the implementation of evidence-based contextual policies, intrahospital management actions, community healthcare facilities, non-pharmaceutical interventions, enhanced surveillance, workplace preventive measures, mental health interventions and communication plans.Conclusion The identified healthcare system strategies applied worldwide to face epidemics or pandemics are a useful knowledge base to inform decision-makers about control measures to be used in the transition phases of COVID-19 and beyond.